2002
DOI: 10.1042/bj3610277
|View full text |Cite
|
Sign up to set email alerts
|

Sarcolipin uncouples hydrolysis of ATP from accumulation of Ca2+ by the Ca2+-ATPase of skeletal-muscle sarcoplasmic reticulum

Abstract: Sarcolipin (SLN) is a small peptide found in the sarcoplasmic reticulum of skeletal muscle. It is predicted to contain a single hydrophobic transmembrane α-helix. Fluorescence emission spectra for the single Trp residue of SLN suggest that SLN incorporates fully into bilayers of dioleoylphosphatidylcholine, but only partially into bilayers of phosphatidylcholines with long (C22 or C24) fatty acyl chains. The fluorescence of SLN is quenched in bilayers of dibromostearoylphosphatidylcholine, also consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(40 citation statements)
references
References 26 publications
2
38
0
Order By: Relevance
“…This indicates unequivocally that, over the physiological range of transmembrane potentials, SLN forms channels that have a high selectivity for small inorganic anions but are practically impermeable to inorganic cations. The impermeability of vesicle membranes incorporating SLN to protons was reported by Smith et al (6).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This indicates unequivocally that, over the physiological range of transmembrane potentials, SLN forms channels that have a high selectivity for small inorganic anions but are practically impermeable to inorganic cations. The impermeability of vesicle membranes incorporating SLN to protons was reported by Smith et al (6).…”
Section: Discussionmentioning
confidence: 60%
“…In contrast to PLN, SLN has been reported to stimulate maximal Ca 21 uptake rates (V max ) (1,4). However, Smith et al (6) did not detect significant effects of SLN on the rate of ATP hydrolysis by Ca-ATPase or on the Ca 21 -dependence of Ca-ATPase activity; rather, they found that SLN leads to reduced levels of accumulation of Ca 21 by Ca-ATPase through effects on leak and slippage pathways. Although the inhibitory effect of PLN is relieved by its phosphorylation, originally no evidence of SLN phosphorylation was found (1).…”
Section: Introductionmentioning
confidence: 97%
“…Sarcolipin modulates muscle thermogenesis via uncoupling of SERCA-mediated ATP hydrolysis. 29 Parallel ablation of sarcolipin and BAT thermogenic capacity renders mice cold intolerant, and reintroduction of sarcolipin expression in skeletal muscle rescues the phenotype. 30,31 Corroborating an interdependence between BAT and muscle for non-shivering thermogenesis, UCP1 KO mice increase muscle sarcolipin levels in the cold.…”
Section: Discussionmentioning
confidence: 99%
“…The Sarco/Endo-plasmic Reticulum Ca 2+ -ATPase (SERCA) transfers Ca 2+ from the sarcoplasm into the lumen of the sarcoplasmic reticulum, hydrolyzing ATP in the process. Sarcolipin, a small helical peptide, can interact with SERCA and alter the kinetics of Ca 2+ re-sequestration by allowing slippage of Ca 2+ back into the sarcoplasm, thereby 'decoupling' Ca 2+ uptake from SERCA-dependent ATP hydrolysis and creating a futile cycle of Ca 2+ movement that generates heat [68]. In the present study, Ckmm-Cre driven Tsc1 deletion resulted in increased wholebody energy expenditure ( Figure 1D), transcriptional upregulation of both SERCA2 and sarcolipin ( Figure 4C), and increased expression of sarcolipin at the protein level ( Figure 4D).…”
Section: Discussionmentioning
confidence: 99%